Root extraction by Niẓām al-Dīn al-Nīsābūrī (d. ca. 1330/730AH): DOI: 10.48129/kjs.11919 - Abbassi, Ahmed (Kuwait Journal of Science, 2022)
In this article, we discussed root extraction in al‐Ḥasan al- Nīsābūrī (d. Ca. 1330 AD), based on six copies of his manuscripts titled<<Risāla al-Shamsiyya fil-Ḥisāb>>. Most of the studies we’ve consulted present al-Nīsābūrī as a religious scholar, an exegete of the Qur’ān, and linguist, but they haven’t addressed his scientific production especially the mathematical one. Hence, the benefit of this research is to initiate a new investment in the study of the transfer of the mathematical results and concepts between different scientific foci in the Arab-Islamic civilization. This research comes in the light absence of studies that address some important aspects of overall mathematics produced in central Asia. The importance of this study lies in the fact that it represents a link between what was produced in this field in the 13th century, by al‐Ṭūsī(d. 1274) in his Work<<Jawāmi al-Hisāb bi al-Takht wa al-Turāb>> and the 15th century, by al-Kāshī(d. 1429) in his Treatise <<Miftāḥ al-ḥisāb>> in terms of tools, techniques.